Contribution of fat, sugar and salt to diets in the Pacific Islands: a systematic review. Issue 10 (7th January 2019) - Santos, Joseph Alvin; McKenzie, Briar; Trieu, Kathy; Farnbach, Sara; Johnson, Claire; Schultz, Jimaima; Thow, Anne Marie; Snowdon, Wendy; Bell, Colin; Webster, Jacqui
Abstract: Objective: Pacific Island countries are experiencing a high burden of diet-related non-communicable diseases; and consumption of fat, sugar and salt are important modifiable risk factors contributing to this. The present study systematically reviewed and summarized available literature on dietary intakes of fat, sugar and salt in the Pacific Islands. Design: Electronic databases (PubMed, Scopus, ScienceDirect and GlobalHealth) were searched from 2005 to January 2018. Grey literature was also searched and key stakeholders were consulted for additional information. Study eligibility was assessed by two authors and quality was evaluated using a modified tool for assessing dietary intake studies. Results: Thirty-one studies were included, twenty-two contained information on fat, seventeen on sugar and fourteen on salt. Dietary assessment methods varied widely and six different outcome measures for fat, sugar and salt intake – absolute intake, household expenditure, percentage contribution to energy intake, sources, availability and dietary behaviours – were used. Absolute intake of fat ranged from 25·4 g/d in Solomon Islands to 98·9 g/d in Guam, while salt intake ranged from 5·6 g/d in Kiribati to 10·3 g/d in Fiji. Only Guam reported on absolute sugar intake (47·3 g/d). Peer-reviewed research studies used higher-quality dietary assessment methods, while reports from national surveys had better participation rates but mostly utilized indirect methods to quantify intake. Conclusions: Despite the established and growing crisis of diet-related diseases in the Pacific, there is inadequate evidence about what Pacific Islanders are eating. Pacific Island countries need nutrition monitoring systems to fully understand the changing diets of Pacific Islanders and inform effective policy interventions.